114k views
2 votes
Suppose that when you factor 4t^6-r^10, you get (2t^x+r^y)(2t^x-r^y). determine the sum of t and r.

User Jaskiratjd
by
4.8k points

1 Answer

3 votes

Answer:

8

Explanation:

Given the expression

4t^6-r^10 we are to factorize in the form;

(2t^x+r^y)(2t^x-r^y)

First we need to factorize (2t^x+r^y)(2t^x-r^y)


= (2t^x+r^y)(2t^x-r^y)\\= 4t^(2x)-2t^xr^y + 2t^xr^y - r^(2y)\\= 4t^(2x)-r^(2y)

Compare
4t^(2x)-r^(2y) \ with \ 4t^6-r^(10)


4t^(2x) = 4t^6\\t^(2x) = t^6\\equate \ the \ powers\\2x = 6\\x = 3\\

Get y;


r^(2y) = r^(10)\\2y = 10\\y = 5\\Hence \ x + y = 3+5 = 8

Hence the sum of x and y is 8

User Deera Wijesundara
by
5.5k points